Clinical efficacy of transjugular intrahepatic portosystemic shunt in the treatment of hepatopulmonary syndrome. Issue 49 (December 2017) - Zhao, Hongwei; Liu, Fuquan; Yue, Zhendong; Wang, Lei; Fan, Zhenhua; He, Fuliang
Abstract : Abstract: Transjugular intrahepatic portosystemic shunt (TIPS) reduces the portal venous pressure of patients with hepatopulmonary syndrome (HPS). To describe the patients who underwent TIPS for the treatment of HPS. A retrospective study was performed on 81 patients with HPS and gastrointestinal hemorrhage treated with TIPS. Thirty patients underwent TIPS through the main portal vein (group A), 24 through the left branch of the portal vein (group B), and 27 through the right branch of the portal vein (group C). The partial pressure of arterial oxygen (PaO2 ), alveolar-to-arterial oxygen partial pressure gradient (A–aPO2 ), oxygen saturation (SO2 ), and complications were recorded and compared. The survival rate for each group was calculated. The technical success rate was 100% in the 3 groups. Preoperative portal vein pressure showed no significant differences between the 3 groups, which was decreased post-TIPS operation. In group A, PaO2 and SO2 were higher in 15 days and 3 months postoperative than preoperative ( P  < .05), whereas A–aPO2 was lower ( P  < .05). No difference occurred between 12 months post- and preoperative group. In group C, PaO2 and SO2 did not alter significantly at each time point after operation ( P  > .05), whereas A–aPO2 decreased at 3 months ( P  = .041) than preoperative. In group B, all indicators at each follow-up time point after TIPS were improved significantly as compared with the preoperative group ( P  < .05), which showed an excellent effect on hypoxemia treatment. Although the 1-year survival rate of 3 groups of patients was 92.85%, 90.90%, and 91.67%, respectively, the rate of hepatic encephalopathy and hepatic myelopathy was 33.33% (10/30), 16.67% (4/24), and 33.33% (9/27) after TIPS. TIPS reduced the pressure of the portal vein effectively and alleviated hypoxemia in most HPS patients successfully. Thus, the left branch of the portal vein is optimal for TIPS owing to fewer complications and efficacy in improving PaO2 as compared with the main portal vein and right branch.